2021
DOI: 10.1021/acs.jafc.1c03831
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Azaspiracids 1–3 with a Hepatopancreatic Fraction from Blue Mussels (Mytilus edulis)

Abstract: Azaspiracids (AZAs) are a group of biotoxins produced by the marine dinoflagellates Azadinium and Amphidoma spp. that can accumulate in shellfish and cause food poisoning in humans. Of the 60 AZAs identified, levels of AZA1, AZA2, and AZA3 are regulated in shellfish as a food safety measure based on occurrence and toxicity. Information about the metabolism of AZAs in shellfish is limited. Therefore, a fraction of blue mussel hepatopancreas was made to study the metabolism of AZA1–3 in vitro. A range of AZA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Corresponding results were obtained from analysis of the doubly labelled AZA3 at 77 h reaction time (Figures S13 and S14 ). The m / z 125.0597 ion does not appear to involve C-1, C-3, C-8, C-21, C-22, or C-23, as this ion was observed in LC–HRMS/MS spectra of known AZAs and their metabolites [ 17 , 33 ] as well as in a synthetic specimen of the C-1 alcohol analogue of AZA3 (Figure S15 ). The finding that ring-B is involved in 18 O-exchange under weakly acidic conditions, presumably via opening of the ketals at C-10 and/or C-13, provides a possible explanation of the observed instability of AZA2 under these conditions.…”
Section: Resultsmentioning
confidence: 89%
“…Corresponding results were obtained from analysis of the doubly labelled AZA3 at 77 h reaction time (Figures S13 and S14 ). The m / z 125.0597 ion does not appear to involve C-1, C-3, C-8, C-21, C-22, or C-23, as this ion was observed in LC–HRMS/MS spectra of known AZAs and their metabolites [ 17 , 33 ] as well as in a synthetic specimen of the C-1 alcohol analogue of AZA3 (Figure S15 ). The finding that ring-B is involved in 18 O-exchange under weakly acidic conditions, presumably via opening of the ketals at C-10 and/or C-13, provides a possible explanation of the observed instability of AZA2 under these conditions.…”
Section: Resultsmentioning
confidence: 89%
“…Treatment of these three compounds with blue mussel hepatopancreas caused production of numerous other AZAs, including several new congeners as detected by MS, therefore monitoring of the three parent compounds alone may be insufficient as a food safety measure. 353 A recent study has shown that gambierone from Gamberidiscus cheloniae is not as toxic as other ciguatera components. 354 Brevetoxin PbTx-2 has differential effects against human and dinoagellate thioredoxin reductases, suggesting it is a key endogenous regulator of this enzyme in K. brevis.…”
Section: Dinoagellatesmentioning
confidence: 99%
“…Treatment of these three compounds with blue mussel hepatopancreas caused production of numerous other AZAs, including several new congeners as detected by MS, therefore monitoring of the three parent compounds alone may be insufficient as a food safety measure. 353…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…In mussels, the expression of AZA-1-3 can lead to the production of AZA-8, AZA-12, and AZA-5 through C-23 α hydroxylation. Additionally, the double hydroxylation of AZA-67 and AZA-68 can generate AZA-1 and AZA-2 as secondary metabolites [14].…”
Section: Synthesis In Vivomentioning
confidence: 99%
“…Among these, Azadinium dexteroporum is currently known to produce the highest number of AZA variants, with up to six types reported [13]. The total number of named AZA toxins and their analogs currently stands at AZA-68 [14]. (Table 2).…”
Section: Introductionmentioning
confidence: 99%